Audit Energi Listrik dan Air Serta Analisis Peluang Hemat Energi di Hotel Uma Ubud Bali - I Nyoman Oka Suryatmaja; I Wayan Suriana; I Made Asna; I Wayan Sukadana (Jurnal Ilmiah Telsinas, 2020)
The use of electrical energy and water is very critical in the hotel industry because of almost all operational equipment support are uses electrical energy and most of the hotel operation using water. However the use of electrical energy and water should be used efficiently. According to Government Regulation No. 70 year 2009 Article 10 (1), that individuals, business entities and permanent establishments in energy supply activities are obliged to carry out energy conservation. This process includes an Energy Audit, which is a method to calculating energy use in a building where the results obtained to be compared with the existing standards so that it can be seen whether the energy use in the building is efficient or not. The standard used is the USAID-ASEAN Energy Consumption Intensity (IKE), which is 300 kWh/m2/year for the electricity standard and for the water standard is using USAID|Indonesia Water Consumption Intensity (IKA) which the standard for Bali area is 3.48 m3/room occupied/year. The Energy Audit at hotel Uma Ubud Bali is obtained an IKE of 207.78 kWh/m2/year and an IKA is 2.58 m3/room occupied/year so that it can be said that the use of electricity and water at hotel Uma Ubud Bali is likely to be inefficient, so an analysis of Energy Saving Opportunities (PHE) is needed. Energy Saving Opportunities at the hotel Uma Ubud Bali can be implemented in periodic AC maintenance, the use of motion sensors, replacing conventional water heaters with heat pumps, reducing the pool water pump operating hours, replacing inefficient light bulbs into LED light and maximizing of using grey water from waste water treatment plant to watering plantation and irrigating fishpond. Keywords: Energy Audit, IKE, IKA and PHE